2019
DOI: 10.1136/heartjnl-2019-315680
|View full text |Cite
|
Sign up to set email alerts
|

Current state of home-based exercise interventions in patients with congenital heart disease: a systematic review

Abstract: Home-based exercise training is a promising alternative to conventional supervised training for patients with congenital heart disease (CHD). Even though the beneficial effect of exercise interventions is well established in patients with CHD, knowledge concerning variety and utility of existing programmes is still lacking. Therefore, the aim of this review is to give an overview about existing home-based exercise interventions in patients with CHD. A systematic search was performed in PubMed, Cochrane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 44 publications
1
24
0
Order By: Relevance
“…In addition to supervised training sessions, children were encouraged to stay active throughout the week, participating in physical education at school and non-competitive games. Regarding respiratory training, as the protocol had to be trained three times a week, two of them were performed during the sessions, while the other one was carried out at home [30]. Patients received a guide and registered session completion and incidents.…”
Section: Interventionmentioning
confidence: 99%
“…In addition to supervised training sessions, children were encouraged to stay active throughout the week, participating in physical education at school and non-competitive games. Regarding respiratory training, as the protocol had to be trained three times a week, two of them were performed during the sessions, while the other one was carried out at home [30]. Patients received a guide and registered session completion and incidents.…”
Section: Interventionmentioning
confidence: 99%
“…Healthcare professionals should raise awareness of these online classes to their patients, in order to help them meet and maintain recommended levels of activity despite closure of fitness centers. A systematic review investigating home based exercise programmes for patients with ACHD found these to be a safe and feasible alternative to cardiac rehabilitation, which reaffirms the efficacy of this proposed intervention (10,18) .…”
Section: Impact Of the Covid-19 Pandemicmentioning
confidence: 67%
“…The small sample sizes in some studies were probably due to restrictive inclusion criteria, such as only limited to specific CHD cohorts and surgical procedures 30 36 37 39 44 ; furthermore, only four studies included comparisons with a healthy control 35 38 43 Exercise prescription is only as effective as participants' adherence, which was poorly described in most studies. 67 Therefore, acquiring patient and public involvement prior to any intervention could be beneficial in accommodating patients' and parents' expectations and abilities and increase the chances of higher adherence. 67…”
Section: Reviewmentioning
confidence: 99%